The Influence of Leadership and Motivation on Employee Work Discipline at Fave Hotel Olo Padang - Sanotona Duha, Suranto; Yuliana, Yuliana (Universitas Negeri Padang, 2024)
The study was undertaken to explore how leadership and motivation impact employee work discipline at Fave Hotel Padang. The primary objective is the investigation of the correlation between leadership, motivation, and work discipline. The research methodology employed was quantitative in nature. The data utilized in the study comprised both primary and secondary sources. The study's target population encompassed the staff of Fave Hotel Padang. A sample size of 30 employees was selected using a non-probability sampling technique. Data collection was facilitated through a questionnaire designed with a Likert scale, which was pretested for validity and reliability. The collected data were subjected to analysis using SPSS 25.00 software.The findings of the study revealed that leadership was classified as moderately satisfactory (46.67%). Furthermore, the motivational aspect was rated positively (80%), while the variable of work discipline garnered an agreeable response (76.67%). The influence exerted by leadership (X1) and motivation (X2) on work discipline (Y) was determined to be 24.1% and 75.9% respectively, with other factors contributing to the remaining impact. Further analysis unveiled that the leadership variable (X1) displayed a Beta or Standardized Coefficient value of 0.086, surpassing the threshold of 0, accompanied by a T-count value of (0.400) with a significance level of 0.002, lower than 0.05. Hence, it can be deduced that the leadership variable (X1) exhibits a significant and favorable impact on work discipline (Y). Similarly, the hypothesis stemming from the motivation segment of the research displayed a Beta or Standardized Coefficient value of 0.110, surpassing the threshold of 0, coupled with a calculated T-value of (0.511) at a significance level of 0.013, also less than 0.05. This underscores the fact that the motivational (X2) significantly and positively affects work discipline (Y).